2021
DOI: 10.1101/2021.03.03.21252806
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic review of the effects of pandemic confinements on body weight and their determinants

Abstract: Pandemics and subsequent lifestyle restrictions such as lockdowns may have unintended consequences including alterations in body weight. Understanding the impact and the mechanisms affecting body weight is paramount for planning effective public health measures for both now and future lockdown-type situations. This systematic review assesses and the impact of pandemic confinement on body weight and to identifies contributory factors. A comprehensive literature search was performed in seven electronic database… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 98 publications
(391 reference statements)
1
20
2
2
Order By: Relevance
“…However, many reports during COVID-19 show that despite a small increase in population weight/BMI, many individuals have experienced a reduction in weight/BMI [9,10,[13][14][15][16][17]. The average weight increase/decrease reported in this study are larger than the 0.6-3.0kg/2.0-2.9kg average weight increase/decrease reported in a systematic review of COVID-19 studies, until July 2020 [7].…”
Section: Comparison To Previous Studiescontrasting
confidence: 63%
See 3 more Smart Citations
“…However, many reports during COVID-19 show that despite a small increase in population weight/BMI, many individuals have experienced a reduction in weight/BMI [9,10,[13][14][15][16][17]. The average weight increase/decrease reported in this study are larger than the 0.6-3.0kg/2.0-2.9kg average weight increase/decrease reported in a systematic review of COVID-19 studies, until July 2020 [7].…”
Section: Comparison To Previous Studiescontrasting
confidence: 63%
“…at the start of the pandemic), as initial dietary changes have been associated with maintaining pandemic weight gain [12]. The time-varying behavioural predictors included HFSS snacks intake, HFSS meals intake, fruit and vegetables intake, physical activity (reduced physical activity vs all other, given the link between reduced physical activity and pandemic weight gain [7,10,21], based on WHO weekly physical activity recommendations of two days per week for strengthening physical activity, and 150 minutes per week for aerobic physical activity [31]), alcohol consumption (£14 weekly units vs >14 weekly units, based on government low-risk drinking recommendations [32]) and smoking status (yes vs no). HFSS foods intake, physical activity and alcohol consumption were assessed at each wave using standard measures (see supplementary material).…”
Section: Explanatory Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, such preventive measures caused significant changes of lifestyle and dietary habits, with potential influence on metabolic health in the general population. In particular, a weight gain was often reported both in children 27,28 and in adults 29‐32 . A recent systematic review found that the social containment measures due to the COVID‐19 lockdown generated a weight gain in 7.2%‐72.4% of subjects 31 …”
Section: Discussionmentioning
confidence: 99%